2010
DOI: 10.1021/ja105617z
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient Metal-Free Growth of Nitrogen-Doped Single-Walled Carbon Nanotubes on Plasma-Etched Substrates for Oxygen Reduction

Abstract: Abstract:We have for the first time developed a simple plasmaetching technology to effectively generate metal-free particle catalysts for efficient metal-free growth of undoped and/or nitrogen-doped single-walled carbon nanotubes (CNTs). Compared with undoped CNTs, the newly produced metal-free nitrogen-containing CNTs were demonstrated to show relatively good electrocatalytic activity and long-term stability toward oxygen reduction reaction (ORR) in an acidic medium. Owing to the highly generic nature of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
442
1
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 624 publications
(455 citation statements)
references
References 36 publications
11
442
1
1
Order By: Relevance
“…Precursors containing carbon and hetero atoms are introduced simultaneously and then deposited onto the surface of the nanochannels, thus yielding outer surface doped CNTs. N and B are the most widely used hetero atoms for the doping of CNTs [102][103][104][105].…”
Section: Hetero Atom Doping Of the Aao-cntsmentioning
confidence: 99%
“…Precursors containing carbon and hetero atoms are introduced simultaneously and then deposited onto the surface of the nanochannels, thus yielding outer surface doped CNTs. N and B are the most widely used hetero atoms for the doping of CNTs [102][103][104][105].…”
Section: Hetero Atom Doping Of the Aao-cntsmentioning
confidence: 99%
“…Generally, they have been synthesized with the help of metal catalysts (e.g Co or Fe), which had raised the concern that the ORR activity was attributable to the metal-nitrogen complexes as in the well-known case of metal-porphyrins [9]. However, synthesis methods that do not use any metal precursors or catalysts have been recently developed and ORR activity of the catalyst has been preserved [15,[18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…graphene [10,[23][24][25][26][27][28][29][30][31][32][33], carbon nanotubes [11,20,21,[34][35][36][37][38][39][40][41][42][43], carbon nanofibers [12,[44][45][46][47], mesoporous carbon [15,22], graphitic carbon [48,49], carbon spheres [19,[50][51][52][53], carbon nanocages 4 [54], flower-like carbon [55], carbon aerogel [56,57], vesicular carbon [58], nanodiamonds [59]) relatively few have been tested in actual fuel cell conditions [58,[60][61][62]…”
Section: Introductionmentioning
confidence: 99%
“…Whereas the majority of recent studies on carbon nanostructured metal-free electrocatalysts focus on ORR reactions in alkaline electrolytes, fuel cells that operate with acidic electrolytes, particularly polymer electrolyte membrane fuel cells (PEMFC) [14,15], can have a more significant economic impact. Therefore, the development of effective metal-free carbon-based catalysts for acidic electrolytes is important, though still challenging [16,[145][146][147][148][149][150].…”
Section: Carbon-based Metal-free Orr Electrocatalysts For Fuel Cellsmentioning
confidence: 99%
“…N,S-co-doped CNTs (NS-CNTs) were also demonstrated to show enhanced ORR activity compared with CNTs, NCNTs, and SCNTs [150] with a much better durability than that of commercial 20 wt% Pt/C catalysts. Other examples of metalfree electrocatalysts for ORR in acidic electrolytes include N-doped SWCNTs [145], vapor-phase-polymerized PEDOT [152], pyridinic and pyrrolic N-doped graphene prepared by confined polymerization/carbonization within layered montmorillonite [90], graphene/CNT layer-by-layer composites [153], and N,F-co-doped graphite nanofibers [154]. Using pyrolysis of sulfur-doped rGO in the presence of Nafion and dimethyl formamide at 600 °C, Pham et al [17] reported the synthesis and characterization of F,N,S-tri-doped reduced graphene oxide (F,N,S-rGO) in both acidic and alkaline PEFCs (Fig.…”
Section: Carbon-based Metal-free Orr Electrocatalysts For Fuel Cellsmentioning
confidence: 99%